The Analysis of Irrigation Water Shortage Percentage in Ho Watershed During the Dry Season - Walbat , Florinaus; Tika, I Wayan; Madrini , Ida Ayu Gede Bintang (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Irrigation water shortageis caused by insufficient water discharge during the dry season. The water is distributed unevenly; theupstream water tends to have a surplus water,whereas the downstream has the tendency of water deficit. Based on the situation,it is necessary to conduct researchon the irrigation watershortageduring the dry season, so that optimal water management can be achieved. The study was conducted to determine the percentage of irrigation water deficiency in each subak and determine irrigation water management techniques that ensuring the water distributed evenly to each subak.Primary data were obtained by interview, observation, and measurement methods, while secondary data were obtained from BMKG Region III Denpasar. The data obtained were analyzed to determinethe percentage of irrigation water shortages that occurred during the dry season and to determine the proportion of irrigation water distribution.The results showed that the percentage of water shortage of irrigation water in the upstream subak was -48,43%, in the middle subak was 21,99%, and in the downstream subak 23,92%.Theproportional water management techniques in the upstream subak, middle,downstream in the dry season using modified Qt, the upstream subakhadthe initial Qt of 2,67 l/sec/haand themodified was 1,73 l/sec/ha, in the middle subak has the initial Qt of1,32 l/sec/ha and the modified was0,75 l/sec/ha, and in the downstream subak had initial Qt of 2,53 l/sec/haand themodified onewas3,21 l/sec/ha.